Park Rangers as Public Health Educators: The Public Health in the Parks Grants Initiative - Wong, David (American Public Health Association, 2010)
Health education in nontraditional settings can supplement messages received in more traditional venues, such as schools and health care facilities, and can reach new populations. In 2007, the US National Park Service awarded one-time seed grants of $10 000 or less to 16 parks in 16 states to fund the development of public health–focused programs for visitors. These programs used a wide variety of formats and addressed topics such as air pollution, prevention of vector-borne diseases, and promotion of physical activity in the parks. Almost 12 000 visitors attended the programs in 2007. Most programs were supported by park management and were well received by visitors. National parks and similar settings may be underutilized resources for delivering health messages to the general population.